Precipitation drives latitudinal patterns of multifaceted biodiversity in montane forests, South-Central China - Hongjie Meng; Lin Chu; Pengcheng Wang; Xinzeng Wei; Jianming Liu; Mingxi Jiang (Ecological Indicators, 2025)
Understanding the spatial distribution characteristics and underling mechanisms of taxonomic, phylogenetic and functional diversity is crucial for advancing global biodiversity conservation. Here, we investigated the latitudinal and longitudinal patterns of multifaceted biodiversity of montane forest in a biodiversity hotspot, South-Central China. Multiple linear regression and hierarchical analysis were used to identify the critical factors affecting biodiversity. The results concluded that the latitudinal patterns of taxonomic, phylogenetic, and functional diversity were congruent with the latitudinal diversity gradient from the equator to the poles. Climatic and edaphic factors, particularly precipitation, played a crucial role in spatial patterns of biodiversity. Climatic and edaphic variables simultaneously explained 48%-66% of the spatial variation of multidimensional diversity, except Rao’s phylogenetic quadratic entropy. There were significant associations among multiple measures of diversity in subtropical montane forests. High water availability and low seasonal variation underlie the greater coexistence of tree species at low latitudes. These results present robust evidence for congruent latitudinal patterns of taxonomic, phylogenetic, and functional diversity, and provide a striking explanation that the same filtering effects of precipitation result in positive relationships among multifaceted diversity. Species richness might be a reliable indicator of taxonomic, phylogenetic, and functional diversity, and may be reasonably applied for conservation planning and forest management in subtropical montane regions.